Penerapan Pembelajaran PMRI dalam Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas III SD Negeri 87 Ambon pada Materi Luas Bangun Datar - Econ Kabiran (MATEMATIKA DAN PEMBELAJARAN, 2017)
This research aims to increase: (1) student activity; (2) mathematics learning result of student class III at SD N 87 Ambon, during process of learning mathematics with application of PMRI. The research subject of 35 students class III at SD N 87 Ambon with 3 collaborators. This research including Classroom Action Research (CAR) using the model of Kemmis and Taggart with 2 cycles. The collected data were through tests, observations, field notes, questionnaires, and documentation. Data analysis used descriptive statistics with the percentage and model jalur. The results of this research showed that, student activities increased by 27,89% from 57,59% to 85,48% of cycle I to cycle II with application of learning PMRI. Then, an increase learning results is characterized by the number of students class III at SD N 87 Ambon who completed learn before giving the action at 20% (7 of 35 students) increased by 42,86% in cycle I to 62,86% (22 of 35 students) and re-increased by 31,43% in the second cycle to 94,29% (33 of 35 students). From the above explanation can be concluded that the application of learning PMRI can increase activities and learning student of class III at SD N 87 Ambon on material Area of The Plane Figure. Keywords: Indonesian version of Realistic Mathematics Education (PMRI), Student Activity, Learning Result, Area of The Plane Figure